Čustveno doživljanje žensk, obolelih za rakom dojke in doživljanje vloge medicinskih sester pri psihični podpori - Šmit, Majda (Obzornik zdravstvene nege, 2004)
The article deals with the psychosocial impact of breast cancer on the experiencing of patients. The aim of the study was to learn about emotional experiencing of women and their perception of the role of the nurse. The author analysed case studies of five women with breast cancer. The data were gathered by means of interviews performed on March 2002. The gathered records of all interviews were processed by means of qualitative analysis of the texts. The analysis revealed the highest percentage of negative emotional states in patients in periods of diagnostic process and early treatment. The patients consulted nurses in most cases during the continuation of therapy of chemotherapy ward. In conclusion the author stresses the need for postgraduatetraining in oncological nursing care which would enable nurses to perform holistic care for patients with breast cancer, and presents three propositions: preparation of additional printed materials and announcements, organization of consulting rooms and telephone counseling for women and their relatives.
Keywords: bolniki; breast; Breast Neoplasms; čustva; Dojka, novotvorbe; dojke; kirurško zdravljenje; Medicinska sestra-bolnik, odnosi; medicinske sestre; Nurse-Patient Relations; Nursing; psihologija; Psychology; rak (medicina); samopodoba; zdravstvena nega